Dental caries and periodontal disease prevalence and oral hygiene practices among Chepang female of Nepal - Pradhan, Reema Joshi; Poudyal, Sijan; Lamichhane, Ramsudhan; Joshi, Ujjwal (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aim: To explore the dental caries and periodontal disease and oral hygiene practice among the females in Chepang ethnic group. Methods: Questionnaire were developed regarding socio-behavioral aspects in the prevention and control of dental caries and periodontal diseases at an individual and population level; and mechanical and chemical plaque control in the simultaneous management of gingivitis and dental caries. Data were collected and analyzed. Results: Total 104 female patients were interviewed with their mean age of 30.1±12.7 (range: 11-70) years. 85.6% showed the regular brushing and 96.2% used the tooth brush and paste. 79% of the female brushes twice daily. Periodontal index and DMFT index showed good results. Conclusions: Despite of tooth brushing practice the prevalence of periodontal disease and DMFT were significant. This could be associated with many other factors. Education and motivation of the population is required to improve the oral hygiene, oral hygiene measures and to refrain from habits. Keywords: Caries, Chepang female, DMFT, Periodontal Index